RESPON SISTEM FLUVIAL TERHADAP PERUBAHAN IKLIM PLISTOSEN AKHIR-HOLOSEN TERKAIT SIKLUS MILANKOVITCH (Studi kasus geologi Kuarter berdasarkan aspek sedimentologi dan stratigrafi di dataran rendah pantai Pekalongan, Jawa Tengah) - Herman Moechtar; Herman Mulyana (Jurnal Geologi dan Sumberdaya Mineral, 2010)
The study consist of sedimentology and stratigraphy analyses of fiveteen boreholes along the NW-SE and N-S, starting from near shorelines to the southern area. The depth of bore hole varies from 9.25 to 14.80 m. The Late Pliestocene-Holocene sediments in the studied area have been correlated, using ceoss section in 1:100 scales. The sediments consist of offshore, nearshore, beach, swamp, river channel, and floodplain deposits. The study is focused in the river channels. The changing vertically and laterally of river channel show the effects of climate and tectonic. During fluvial systems (IP II and IP III) depositional process, show climatic changes on Milankovitch cycles involving a stage episode from the middle of sub-humid (D2/ late warming) to the late sub-humid (B1/ early cooling). River channel shifting due to laterally base level change is influenced by tectonic.Keywords: River channel, climate, Late Pleistocene-Holocene